Trends in the use of bentonite clays - A. S. Panasyugin (Litʹë i Metallurgiâ, 2020)
The paper gives a general description of the areas of application of bentonite clays. A number of deposits were evaluated in terms of their use in various technological processes. Analysis of directions of application of bentonite clays in foundry was carried out.Using the methods of X-ray and gas chromatographic analysis, scanning electron microscopy, thermogravimetry and direct adsorption-structural measurements, it is shown that materials obtained from montmorillonite and heteronuclear hydroxo complexes Cr-Cu have greater thermal stability and better sorption characteristics compared to montmorillonite fixed by mononuclear hydroxo complexesUsing montmorillonite modified with heteronuclear hydroxo complexes Cr-Cu with the best adsorption-structural parameters and zeolite NCVM, a laboratory batch of mixed adsorbent catalysts has been developed.This material has been studied in deep vapor oxidation processes of low concentrated organic substances such as acetone, toluene, ethyl acetate, ethanol, butanol and butyl acetate.The conversion rate on the mixed adsorbent catalysts for the studied adsorbates was found to be 94.9–97.7 (average 96.2 %).